'Always like never before': learning from the lumitopia of Tivoli Gardens. (2nd September 2019) - Edensor, Tim; Bille, Mikkel
Abstract: Drawing on a detailed analysis of the historical and current development of lighting in Copenhagen's Tivoli Gardens, this article addresses how this site of extraordinarily diverse illumination exemplifies a carefully orchestrated balance between (1) muted and more vivid forms of lighting, (2) curation of historical styles and promotion of contemporary innovations in illumination and (3) artistic luminaires and those more aligned with popular tastes. Through these themes, we argue that the current strategies towards urban lighting that predominantly promote energy conservation, security, commercial imperatives and place-branding may be supplemented by place-specific design strategies that implement multiplicity, connect past and present, and accommodate diverse desires, dreams and realities. These attributes contribute to the ongoing emergence of what we call a 'lumitopia', a space in which an intensified attention to illumination is integral to the particularity of a place or landscape. In the case of Tivoli, this offers a lens to manage nocturnal space so that it becomes more aesthetically complex, inclusive and convivial.